Surgical Strategies: Necrotizing Fasciitis of the Foot and Ankle Treated With Dermal Regeneration Matrix for Limb Salvage. (January 2021) - Narayanan, Arvind S.; Walley, Kempland C.; Borenstein, Todd; Luther, G. Aman; Jackson, J. Benjamin; Gonzalez, Tyler A.
Although necrotizing fasciitis is a life-threatening entity that needs expeditious treatment, cases involving the lower extremity are less commonly encountered than in the upper extremity. Surgical intervention is often required and likely lead to amputation (below-knee or above-knee) vs debridement in the lower extremity. Coverage options in the foot and ankle after serial debridements can present many challenges for limb salvage. Patients are often left with large soft tissue defects requiring coverage with a subsequent increase in relative morbidity. Treatment options for coverage in these cases include negative-pressure wound therapy, split-thickness skin grafting, free flap coverage, or higher-level amputation. In the diabetic population, who present with a lower extremity necrotizing infection, limb salvage is often a challenge given the multiple comorbidities associated with these patients including peripheral vascular disease, immunocompromised state, and neuropathy. Optimal treatment strategies for these necrotizing infections in the foot and ankle remain uncertain. We offer a technique tip for utilization of a dermal regeneration matrix to allow coverage of large soft tissue defect with exposed tendon and/or bone without the need for free flap coverage or higher-level amputation, thus allowing for an additional limb salvage option. Level of Evidence: Level V, expert opinion.